pelatihan Pelatihan Pembuatan Pie Pisang Sebagai Makanan Khas di Desa Kandangtepus Kecamatan Senduro Kabupaten Lumajang: Pelatihan Pembuatan Pie Pisang Sebagai Makanan Khas di Desa Kandangtepus Kecamatan Senduro Kabupaten Lumajang - suci ristiyana; Ahmad Ilham Tanzil; Tri Wahyu Saputra; Ika Purnamasari (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Kandangtepus Village is an area where the majority of the people grow Kirana bananas, and its marketing has penetrated the export market. Kandangtepus village produces the famous banana, Mas Kirana banana. However, the area does not yet have a typical food processing from the base of bananas which can increase the price of Kirana bananas in the future other than as an export commodity. Therefore, for this service, we chose a training activity for making banana pie which is expected to later become a special food in the Kandangtepus area and can be known to the wider community outside Lumajang. Banana pie has good nutritional content for the health of the human body, one of which is for digestion, besides that the nutritional content contained in banana pie / 50 grams is as follows: calories 158 kcal, fat 8.05 grams, protein 1.5 grams, carbohydrates 21.3 g, 1.3 g fiber, 10.7 g sugar, 187 mg sodium, 32 mg potassium, 0 mg cholesterol. It is hoped that by making banana pie, the community is more creative and has more skills so that it can improve the welfare of the community, especially in the village